Career Development and Planning Issues for Rural Adolescent Girls - Shepard, Blythe; Marshall, Anne (Canadian Journal of Counselling and Psychotherapy, 2007)
Life-career planning and counselling often highlights a dilemma for young women, who feel torn by conflicting values around work and family. This situation is particularly challenging for young women living in rural communities because they may have limited access to role models. In this qualitative study, eight young women describe how they experienced growing up in a rural environment and the impact of that experience on their future plans. Several metathemes emerged from their narratives which have practical relevance for counsellors who are helping youth to shape their futures.